Rancang Bangun Sistem Informasi Incident Reporting Berbasis Web Pada Polres Gresik - Sofriansyah, Achmad Triadianto; Hartati, Sulis Janu; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Abstract: Police Department is one of the functions of govermment in country, maintenance of security and good order of society, law enforcement, protection, auspices and public service (Indonesian Police Department, 2002). Every day, case or incident often occur arround us.Therefore, Police have to do reporting occurrence or in termed as (incident reporting) to record all incident. Incident categorized into 2 types, criminal (theft, robbery, and other) and non criminal (fires, landslides, and other). To overcome the problems that exist today, then I made a new system were underway that would later help Police department especially GRESIK Police Department Resort in doing incident reports. This new system is expected to overcome the problems especially incident reporting in GRESIK Police Department Resort. This system refers to (Regulation of the head of Police in Indonesian Republic, 2009) which contains with the standart incident reporting.